(untitled) (Economic Journal of Nepal, 2021)
Inflow of personal remittances has exceeded 20 percent of the gross domestic product (GDP) of Nepal for several years. Compared to foreign direct investment (FDI) or foreign aid (grants & loans), the money injected to the economy of Nepal through remittances is markedly larger. Huge investment in the real estate sector and large sums of money applied for share subscription indicate the need and opportunities of channelizing remittances in the infrastructure development and productive sector. However, most studies on remittances are focused on the ex-post analysis of the economy and few studies focus on the planning and policy issues aimed to utilize remittances. This paper reviews literature on utilizing remittance money and analyzes the prospects of capitalizing remittances in Nepal. A conceptual model is proposed on utilizing remittance money for infrastructure development. The proposed model of a remittance investment trust aims to synergize the three best attributes of the three domains of stakeholders, namely, abundant remittance money of the people, excellent management skills of the private sector, and the superior public trust to the government. Remittance money can serve as a great investment vehicle for executing properly investigated and attractive infrastructure projects. As estimated for Lumbini province, the remittance investment trust may contribute to fulfill 20% of the deficit of investment towards achieving the sustainable development goals. While the model is proposed for a province, it is expected to be replicable to the national and sub-national governments in Nepal.